The Use of YouTube Videos in English Teachers' Lesson Plans (RETAIN, 2023)
In this modern era, technology is needed in all aspects of life, including the world of education. Educators began to use internet technology for teaching and learning activities such as the YouTube application. The YouTube app is a platform that allows users to upload, share, live stream and watch videos. Educators may use YouTube videos in their lesson plans. However, educators are sometimes unaware that the selection of video is not in accordance with the learning objectives. This study was conducted to find out what types of videos are used by English teachers and how the suitability or validity between the video's content with learning objectives. A video was valid if the video selection beholds to four aspects, namely the suitability of the video title with the learning objectives, the suitability of video content with learning objectives, the suitability of the video content with the type of text, and the suitability of video content with teaching and learning activities. This study was participated by three junior high school English teachers in Surabaya who filled out a questionnaire. From these three teachers, 11 lesson plans were obtained which can be analyzed using qualitative data analysis, i.e., the case study method. It was found that these three teachers often use learning videos, music videos, and animation videos in their lesson plans. The kinds of YouTube videos include instructional videos, explanation videos in the form of power points accompanied by speaker’s voice, and animated learning videos accompanied by voices and student activities videos. Moreover, from 11 lesson plans, 3 lesson plans were somewhat valid and 8 lesson plans were valid. It can be concluded that the YouTube videos used by the teachers in their lesson plans are mostly valid.